Anti-bacterial and Anti-biofilm Evaluation of Thiazolopyrimidinone Derivatives Targeting the Histidine Kinase YycG Protein of Staphylococcus epidermidis - Lv, Zhihui; Zhao, Dan; Chang, Jun; Liu, Huayong; Wang, Xiaofei; Zheng, Jinxin; Huang, Renzheng; Lin, Zhiwei; Shang, Yongpeng; Ye, Lina; Wu, Yang; Han, Shiqing; et al. (Frontiers in Microbiology, 2017)
Staphylococcus epidermidis is one of the most important opportunistic pathogens in nosocomial infections. The main pathogenicity associated with S. epidermidis involves the formation of biofilms on implanted medical devices, biofilms dramatically decrease the efficacy of conventional antibiotics and the host immune system. This emphasizes the urgent need for designing novel anti-staphylococcal biofilm agents. Based on the findings that compound 5, targeting the histidine kinase domain of S. epidermidis YycG, possessed bactericidal activity against staphylococci, 39 derivatives of compound 5 with intact thiazolopyrimidinone core structures were newly designed, 7 derivatives were further screened to explore their anti-bacterial and anti-biofilm activities. The seven derivatives strongly inhibited the growth of S. epidermidis and Staphylococcus aureus in the minimal inhibitory concentration range of 1.56 to 6.25 µM. All the derivatives reduced the proportion of viable cells in mature biofilms. They all displayed low cytotoxicity on mammalian cells and were not hemolytic to human erythrocytes. The biofilm inhibition activities of four derivatives (H5-32, H5-33, H5-34 and H5-35) were further investigated under shearing forces, they all led to significant decreases in the biofilm formation of S. epidermidis. These results were suggestive that the seven derivatives of compound 5 have the potential to be developed into agents for eradicating biofilm-associated infections.